IDENTIFICATION IN PORE WATERS OF RECYCLED SEDIMENT ORGANIC MATTER USING THE DUAL ISOTOPIC COMPOSITION OF CARBON (δ13C AND Δ14C): NEW DATA FROM THE CONTINENTAL SHELF INFLUENCED BY THE RHÔNE RIVER. Issue 6 (2nd December 2022) - Dumoulin, J-P; Rabouille, C; Pourtout, S; Bombled, B; Lansard, B; Caffy, I; Hain, S; Perron, M; Sieudat, M; Thellier, B; Delqué-Količ, E; Moreau, C; et al.
ABSTRACT: Estuaries and deltas are crucial zones to better understand the interactions between continents and oceans, and to characterize the mineralization and burial of different sources of organic matter (OM) and their effect on the carbon cycle. In the present study, we focus on the continental shelf of the northwest Mediterranean Sea near the Rhône river delta. Sediment cores were collected and pore waters were sampled at different depths at one station (Station E) located on this shelf. For each layer, measurements of dissolved inorganic carbon concentration (DIC) and its isotopic composition ( δ 13 C and Δ 14 C) were conducted and a mixing model was applied to target the original signature of the mineralized OM. The calculated δ 13 C signature of the mineralized organic matter is in accordance with previous results with a δ 13 COM of marine origin that is not significantly impacted by the terrestrial particulate inputs from the river. The evolution with depth of Δ 14 C shows two different trends indicating two different Δ 14 C signatures for the mineralised OM. In the first 15 cm, the mineralized OM is modern with a Δ 14 COM = 100 ± 17‰ and corresponds to the OM produced during the nuclear period of the last 50 years. Deeper in the sediment, the result is very different with a depleted value Δ 14 COM = –172 ± 60‰ which corresponds to the pre-nuclear period. In these two cases, the marine substrate was under the influence of the local marine reservoir effect with more extreme Δ 14 C results. These differences can be largely explained by the influence of the river plume on the local marine DIC during these two periods.